Pengaruh Budaya Perusahaan Dan Komunikasi Terhadap Kinerja Driver Gojek Di Kota Bandar Lampung - Doni, Belly Rama; Komarsyah, Dian; Aprilia, Hani Damayanti (Jurnal Kompetitif Bisnis, 2022)
The purpose of this study was to determine the effect of corporate culture and communication on performance. This study uses a quantitative approach to the type of descriptive research. The sampling technique used is in proportionate stratified random sampling this technique is used because the population is not homogenous. The sample consisted of 100 respondents from gojek drivers. Data obtained from questionnaires distributed, using a Likert scale. The data analysis technique uses multiple regression analysis with the IBM SPSS 25 program test tool. Based on the f (simultaneous) test, it shows that the variables of corporate culture and communication together have a simultaneous influence on performance. Partially shows that the variables of corporate culture and communication have a effect and have a positive direction on performance. Keywords : Corporate Culture, Communication, and Performance